Tinggi Maksimum Selubung Paket Gelombang Bikromatik - Wuryansari Muharini Kusumawinahyu; Andonowati Andonowati (Journal of Mathematical and Fundamental Sciences, 2003)
Previous numerical and experimental investigations found that some envelopes of bichromatics surface water waves show deformation during their propagation along the wave tank in Hydrodinamic Laboratory. In this paper we present investigation on the maximum amplitudes of bichromatics envelopes at every position along the tank, to observe the amplification factor of a signal deformation . As we consider a signaling problem, a spatial Nonlinear Schrodinger (sp-NLS) model is used here. The profiles of waves envelope as a function of time and space are computed numerically from this model. Investigations are done for some different amplitudes and frequencies of bichromatics envelopes at wave generator to show that these two parameters affect the amplification factor and the periode of maximum amplitudes of envelopes.